Eating and image disorders in strength athletes (Research, Society and Development, 2022)
Eating and image disorders are a common reality for strength sports practitioners, who have a strong influence on the environment in the way they conduct dietary strategies and in the way they perceive their own bodies, since they use beautiful bodies to sell a false vision of health. Knowing this, the objectives of this work were to raise awareness about the problem, demonstrate the risk factors, and deliver the main forms of treatment. For this, the bibliographic review method was used to gather several findings on this subject. In the end, it was possible to perceive the risks attributed to the fitness environment and how much these influences can impact the physical and mental health of individuals who start to live in this environment and consume this type of content.